Rapidly Increasing Artificial Iodine Highlights Pathways of Iceland-Scotland Overflow Water and Labrador Sea Water ... - Castrillejo Iridoy, Maxi; Casacuberta, Núria; Vockenhuber, Christof; Lherminier, Pascale (ETH Zurich, 2022)
Iceland-Scotland Overflow Water (ISOW) and Labrador Seawater (LSW) are major water masses of the lower Atlantic Meridional Overturning Circulation (AMOC). Therefore, the investigation of their transport pathways is important to understand the structure of the AMOC and how climate properties are exported from the North Atlantic to lower latitudes. There is growing evidence from Lagrangian model simulations and observations that ISOW and LSW detach from boundary currents and spread off-boundary, into the basin interior in the Atlantic Ocean. Nuclear fuel reprocessing facilities of Sellafield and La Hague have been releasing artificial iodine (129I) into the northeastern Atlantic since the 1960ies. As a result, 129I is supplied from north of the Greenland-Scotland passages into the subpolar region labelling waters of the southward flowing lower AMOC. To explore the potential of 129I as tracer of boundary and interior ISOW and LSW transport pathways, we analyzed the tracer concentrations in seawater collected ... : Frontiers in Marine Science, 9 ...